Study of Multiple resistance Pattern to antibiotic of clinical and Swege E. coli isolates and detection of blaIMP-1 gene by using PCR. (Journal of the College of Basic Education, 2022)
During a 4 months period a dominated pattern of multiple resistance to antibiotic of clinical E. coli isolates which isolated from Central Medicine City hospital / Baghdad ,were analyzed and compared with the multiple resistance pattern of sweges isolates .the results revealed that the multiple resistance pattern of clinical isolates was : CX - CRO – CE- AMC - TR and the pattern of sweages was : CX – CRO- CE- AMC. The isolates which resistant to Cefotaxime , Ceftazidime and Imipenem were selected to detect the ability to Metallo ß -lactamases production (MßLs) .Ten clinical isolates and five swege isolates were able to produce MßLs ,and these isolates were tested to blaIMP-1 by using polymerase chain reaction( PCR) and using Primer : 5- ACC GCA GCA GAG TCT TTG CC – 3 ( F)5-ACA ACC AGT TTT GCC TTA CC _ 3 (R ) Two isolate appeared to carry blaIMP-1 gene after electrophoresis of the results on 1.2% agarose. The results of Bacterial Conjugation experiment between Clinical and Swege isolates showed that the Metallo β-Lactamases were unable to transferred in this process.